Menstrual blood loss as an initial trigger for adaptation of iron metabolism in eumenorrheic female athletes—An exploratory study - Nolte, Svenja; Maier, Celina; Klügel, Simon; Weyh, Christopher; Hacker, Sebastian; Badenhorst, Claire; Krüger, Karsten (Physiological reports, 2025)
Iron deficiency is a risk factor for impaired performance and recovery. While exercise‐related iron losses are well‐documented, the role of menstrual blood loss (MBL) as a physiological trigger of iron regulation remains underexplored. This study examined whether MBL in eumenorrheic female athletes induces measurable hematological and iron‐related responses, accounting for sex hormone fluctuations. Ten regional‐level football players underwent menstrual cycle tracking and venous blood sampling in both the early follicular and mid‐luteal phases. Hematological parameters, iron markers (ferritin and hepcidin), erythropoietic markers (erythropoietin and reticulocytes), and inflammatory markers (myeloperoxidase [MPO] and C‐reactive protein [CRP]) were measured. MBL was assessed using the Pictorial Blood Loss Assessment Chart (PBAC). Analyses included descriptive statistics, correlation, and linear mixed modeling. MBL was significantly associated with ferritin (β = −0.289, p = 0.001), reticulocyte counts (β = 0.004, p = 0.019), and reticulocyte production index (β = 0.004, p = 0.027). MPO and CRP showed inverse correlations with MBL, suggesting potential immunomodulatory effects. No interaction between MBL and cycle phase was found. MBL appears to stimulate compensatory erythropoiesis in female athletes, largely independent of hormonal phase. Incorporating MBL assessment into athlete monitoring may support individualized strategies to maintain iron balance and optimize performance.